Solid-phase synthesis of oligo-2-pyrimidinone-2'-deoxyribonucleotides and oligo-2-pyrimidinone-2'-deoxyriboside methylphosphonates. - Zhou, Y (1996)
A synthetic method was developed for the synthesis of oligodeoxyribonucleotides and oligodeoxyribonucleoside methylphosphonates comprised exclusively of the fluorescent 2-pyrimidinone base for the first time. The method utilized the solid-phase 2-cyanoethylphosphoramidite and methylphosphonamidite chemistry for internucleotide couplings and a baselabile oxalyl linkage to anchor the oligomers onto the CPG support. Cleavage of the oligomers from the support was effected by a short treatment of the support with 5% ammonium hydroxide in methanol at room temperature, without any degradation of the base-sensitive 2-pyrimidinone residues or the base-sensitive methylphosphonate backbone.